2018
DOI: 10.1111/camh.12266
|View full text |Cite
|
Sign up to set email alerts
|

Children's concepts of childhood and adolescent depression

Abstract: Background Research on adolescent Mental Health Literacy (MHL) is rapidly increasing; however, equivalent research in children is lacking. Exploring children's mental health conceptualisations reveals how their knowledge develops and provides the evidence base for the development of mental health education for younger age groups. Methods A total of 105 children aged 8–9 and 11–12 years were interviewed using a vignette methodology structured according to the model of illness representations, exploring: recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Only a handful of studies have sought to determine the relationship between illness beliefs and outcomes such as attitudes towards mental health services and adherence to both psychotropic medication and mental health appointments among youth with anxiety or depression (Munson et al, 2009(Munson et al, , 2010Wisdom & Green, 2004). Existing studies used diverse methodologies, and no consistent theoretical framework of illness belief models exists (Fox, Buchanan-Barrow, & Barrett, 2010;Georgakakou-Koutsonikou et al, 2019;Midgley et al, 2017;Wisdom & Green, 2004), resulting in a disparate literature that lacks a shared language and common theoretical frame, and from which it is difficult to draw firm conclusions.…”
Section: Focus Of This Studymentioning
confidence: 99%
“…Only a handful of studies have sought to determine the relationship between illness beliefs and outcomes such as attitudes towards mental health services and adherence to both psychotropic medication and mental health appointments among youth with anxiety or depression (Munson et al, 2009(Munson et al, , 2010Wisdom & Green, 2004). Existing studies used diverse methodologies, and no consistent theoretical framework of illness belief models exists (Fox, Buchanan-Barrow, & Barrett, 2010;Georgakakou-Koutsonikou et al, 2019;Midgley et al, 2017;Wisdom & Green, 2004), resulting in a disparate literature that lacks a shared language and common theoretical frame, and from which it is difficult to draw firm conclusions.…”
Section: Focus Of This Studymentioning
confidence: 99%
“…First, the prevalence of mental disorders peaks during adolescence. It is a transitional stage characterised by rapid growth and development with the occurrence of numerous physical and psychological changes, such as increased susceptibility to stressors and the emergence of many mental health disorders ( 14 , 17 , 56 , 57 ). Also, previous literature documented that the symptoms of these mental disorders persist throughout childhood; thus, it is not common for intervention programmes to focus on children ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their understanding and engagement can be enhanced through the use of concrete methods, including stories, and specific contextual questions which help to make abstract concepts accessible (Reynolds et al, 2006). The importance of psychoeducation to increase young people's mental health literacy and understanding of mental health difficulties has been highlighted (Georgakakou-Koutsonikou et al, 2019;Georgakakou-Koutsonikou and Williams, 2017). In addition, our findings indicate that some initial psycho-educational work needs to be built into any school-based group programmes provided in this context to help youth understand the core concepts (such as thoughts, feelings and behaviours) that underpin the intervention.…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…Results of another HIC study showed that children as young as 6 or 7 were able to discriminate amongst thoughts, feelings and behaviours, although those 'at risk' of mental health problems performed significantly poorer (Reynolds et al, 2006). Research has shown that most 8-to 12-year-olds can identify emotional difficulties displayed by hypothetical peers in vignettes (Georgakakou-Koutsonikou et al, 2019). Simple, concrete cues, including stories, have also been shown to improve children's (aged 4-7 years) performance in terms of discriminating amongst thoughts, feelings and behaviours (Quakley et al, 2004).…”
Section: Introductionmentioning
confidence: 99%